The term structure of interest rates expectations and behavior patterns - Malkiel, Burton G. 1932- (Princeton University Press, 2016)
Can expectations alone explain the yield differentials among bonds of different maturities? To what extend do attitudes toward risk and transactions costs influence the behavior of bond investors? Is it possible for the Federal Reserve to "twist" the interest-rate structure in accordance with its policy objectives? These are among the questions treated.Originally published in 1966.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905
Im Vorwort: "Teh present study is a revised and expanded version of Part I of my doctoral dissertation, "Problems in the structure of financial markets", submitted to Princeton University in january 1964."
Keywords: Bonds; Interest rates; Hochschulschrift